Disruption of Dense Granular Protein 2 (GRA2) Decreases the Virulence of Neospora caninum - Dong, Jingquan; Zhang, Nan; Zhao, Panpan; Li, Jianhua; Cao, Lili; Wang, Xiaocen; Li, Xin; Yang, Ju; Zhang, Xichen; Gong, Pengtao (Frontiers in Veterinary Science, 2021)
Neospora caninum (N. caninum) causes abortions in cattle and nervous system dysfunction in dogs. Dense granular proteins (GRAs) play important roles in virulence; however, studies on NcGRA functions are limited. In the present study, multiple methods, including site-directed mutagenesis, CRISPR/Cas9 gene editing, western blotting, qPCR, confocal microscopy, plaque, invasion, egress, and replication assays, animal assays of survival rate and parasite burden, and HE staining, were used to characterize the NcGRA2 protein, construct a NcGRA2 gene disruption (∆NcGRA2) strain, and explore its virulence in vivo and vitro. The results showed that NcGRA2 shared 31.31% homology with TgGRA2 and was colocalized with NcGRA6 at the posterior end of tachyzoites and the intravacuolar network of parasitophorous vacuoles (PVs). Cell fractionation analysis showed that NcGRA2 behaved as a transmembrane and membrane-coupled protein. The ∆NcGRA2 strain was constructed by coelectroporation of the NcGRA2-targeting CRISPR plasmid (pNc-SAG1-Cas9:U6-SgGRA2) and DHFR-TS DNA donor and verified at the protein, genome, and transcriptional levels and by immunofluorescence localization analysis. The in vitro virulence results showed that the ∆NcGRA2 strain displayed smaller plaques, similar invasion and egress abilities, and slower intracellular growth. The in vivo virulence results showed a prolonged survival time, lower parasite burden, and mild histopathological changes. Overall, the present study indicates that NcGRA2, as a dense granular protein, forms the intravacuolar network structure of PVs and weakens N. caninum virulence by slowing proliferation. These data highlight the roles of NcGRA2 and provide a foundation for research on other protein functions in N. caninum.